Determinan Penggunaan Aplikasi Audit Tools and Linked Archive System (ATLAS) pada Kantor Akuntan Publik Di Yogyakarta - Ali, Anita Permata Aprilianti; Sa’dani, Olivi Sabilla (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to determine the effect of performance expectations, effort expectations, social influence, and facilitation conditions on the intention to use the Audit Tools and Linked Archive System (ATLAS) application. We conducted the study at Kantor Akuntan Publik (KAP) which spread across Yogyakarta City, including 54 auditors as respondents who passed selection through a purposive sampling method. We collected data through questionnaires and analyzed them using multiple linear regression. The research findings indicate that two main factors, namely performance expectations and facilitation conditions, influence individual intentions to use the ATLAS application. On another note, effort expectations and social influence did not have a significant impact on the intention to use the ATLAS application. Keywords: ATLAS; Performance Expectations; Business Expectations; Facilitation Conditions; Social Influence